2018
DOI: 10.3390/su10082771
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Management Strategies and the Moderating Role of Corporate Social Responsibility in Project Financing Decisions

Abstract: The purpose of this study is to examine the moderating role of corporate social responsibility (CSR) in project financing decisions. CSR has gained growing prominence in today's business era. This study investigates four environmental strategies and the credit risk assessment, stakeholder assessment and corporate social responsibility assessment impact on project financing decision. It explores three main issues related to environmental responsibility (planet), economic responsibility (profit) and social respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 57 publications
0
38
1
1
Order By: Relevance
“…This study also adds implications to the existing literature regarding the link between risk management and sustainability. Although the prior literature has suggested that there is a theoretical connection between risk management and sustainability [2,7,25,38,44], this stream of research is still limited [2,26]. The findings of this study suggest that although there is a positive link between risk management and sustainability, simply adopting risk management elements is not sufficient for ensuring sustainable decision-making.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This study also adds implications to the existing literature regarding the link between risk management and sustainability. Although the prior literature has suggested that there is a theoretical connection between risk management and sustainability [2,7,25,38,44], this stream of research is still limited [2,26]. The findings of this study suggest that although there is a positive link between risk management and sustainability, simply adopting risk management elements is not sufficient for ensuring sustainable decision-making.…”
Section: Discussionmentioning
confidence: 69%
“…Risk management has been viewed as an important practice for improving sustainable decision-making [3][4][5][6][7][8]. Unsustainable behaviors can generate potential business risks to an organization's reputation and ultimately result in the collapse of an organization [9].…”
Section: Introductionmentioning
confidence: 99%
“…The extant literature has revealed that corporate governance not only influences a firm's growth but also affects corporate social responsibility (Bhagat and Bolton, 2019;Zhou, 2019). One study has indicated that corporate social responsibility even influences employee performance in SMEs (Sarfraz et al, 2018a) while, conversely, another emphasizes the moderating role of CSR, which affects project financing (Sarfraz et al, 2018b). However, the CEO is a pivotal figure who can orientate the firm toward adopting CSR measures.…”
Section: Theoretical Background and Hypothesis Formulationmentioning
confidence: 99%
“…Sustainability and Corporate Social Responsibility (CSR) are directly linked as it has been widely demonstrated in the specialized academic literature [63][64][65]. Both terms are, at the same time, starting to be intrinsically connected with a new model of capitalism [66,67].…”
Section: Theoretical Backgroundmentioning
confidence: 97%